Analisis School Well Being Pelajar SMP Yogyakarta melalui REBT pada Pelaku Bullying - Erwan Syah, Muhammad; Juliarti Bantam, Dian (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Unpleasant school experiences due to bullying, whether as a victim or perpetrator, can be a significant source of stress and reduce the quality of life for students (Mathew, 2015). The stress experienced by students will hurt intrapersonal and interpersonal relationships. This will make students feel that the learning climate at their school is unpleasant (Souttera, 2013). This research aims to analyze the effectiveness of SWB through REBT in junior high school students in the city of Yogyakarta. In addition, this research is expected to become the basis for guidance and counseling teaching materials in junior high schools in the city of Yogyakarta. This research is action research carried out by researchers and collaborating with related parties which is adapted to the school situation. The REBT module and SWB measuring instrument used in thiprevious research developmentsprevious researchers' research. The measuring tool used to reveal the SWB of bullying perpetrators is the School Well-Being Scale (SWB Scale). The SWB scale refers to four aspects of SWB, namely having (school conditions), loving (social relationships), and being (self-fulfillment). The results of this research include significant differences in the School Well-Being of the Experimental group which was measured 3 times, namely Pre-test, Post-test, and Follow-up so that Rational Emotive Behavior Therapy was proven to be effective in improving and changing attitudes, perceptions, ways of thinking, beliefs and The irrational view of the bully becomes a rational view. Apart from that, there was an insignificant difference in the control group's School Well-Being which was measured 3 times, namely pre-testcarry-over effects and cofounding factors such as intense interaction and communication between the experimental and control groups caused thisperimental and control groups.